Changes in the structure and D desorptive release from W-D co-deposit layers caused by thermal annealing. (March 2023) - Baldwin, M.J.; Patino, M.I.; Schwendeman, B.; Simmonds, M.; Založnik, A.; Nishijima, D.; Tynan, G.
Abstract: The annealing of ∼ 1 μ m thick tungsten–deuterium co-deposit layers produced at 320 ± 25 K is found to induce changes in the desorptive release behavior and crystal structure. The changes in co-deposits were revealed by annealing in the temperature range 273–1273 K, examining the crystal structure with glancing angle X-ray diffraction, re-populating traps remaining following the anneal, by D plasma exposure at 373 K, then re-examining the co-deposits with glancing angle X-ray diffraction and scanning electron microscopy, before performing thermal desorption mass spectrometry to ascertain the effect of annealing on trap concentrations. The results indicate that low temperature W-D co-deposit layers are prone to the development of a significant fraction of deuterium retention sites, with a predominant thermal release that begins at ∼ 400 K and ceases approaching ∼ 1000 K. Increased annealing temperature is found to progressively depopulate and remove low temperature deuterium retention sites, as suggested by an inability to re-populate those sites with the deuterium plasma. Scanning electron micro-graphs show marked differences at the anneal temperature extremes, with surface conversion from a dendritic appearance at 320 K to a nodular appearance at 1273 K. X-ray diffraction reveals two W phases initially present as 320 K, namely the α -W BCC and β -W A15 crystal phases, the latter of which rapidly anneals out above 490 K leaving only increased Bragg reflection from the α -W phase at the higher annealing temperature. Highlights: Annealed W-D co-deposits reveal changed desorptive release and crystal structure. W-D co-deposit desorption spans ∼ 400 K to ∼ 1000 K. Higher temperature anneals remove low temperature deuterium retention sites. α -W BCC and β -W A15 phases are detected in the co-deposit, but β vanishes above 490 K.